You are Here: Home >< Maths

1. Hello

I am stuck on this:

4x - 3__ __x - 3
-------_ = _-------
1 - 5x__ __x + 7

(Sorry I don't know how to format it right)

So this is what I get, I firstly get rid of the fractions =

(4x - 3)(x + 7) = (x - 3)(1 - 5x)

Expand it out:

4x^2+28x-3x-21 ---> simplied too: 4x^2 +25x -21.

x - 5x^2 - 3 - 15x ---> simplied too: -5x^2 - 14x - 3

4x^2 + 25x - 21 = -5x^2 - 14x - 3

Move it all to one side =

4x^2 + 25x - 21 (+5x^2 + 14x + 3)

9x^2 + 39x - 18

I then try to factorise it...
9 x - 18 = -162... but I can't seem to factorise it, so that tells me I have gone wrong somewhere.

I know the answers are 1 and -1.

Can anyone give me a nudge in the right direction? thank you
2. x - 5x^2 - 3 - 15x

It's supposed to be 15x as -3 * -5 equal 15.
3. (Original post by Tinkletea)
Hello

I am stuck on this:

4x - 3__ __x - 3
-------_ = _-------
1 - 5x__ __x + 7

(Sorry I don't know how to format it right)

So this is what I get, I firstly get rid of the fractions =

(4x - 3)(x + 7) = (x - 3)(1 - 5x)

Expand it out:

4x^2+28x-3x-21 ---> simplied too: 4x^2 +25x -21.

x - 5x^2 - 3 - 15x ---> simplied too: -5x^2 - 14x - 3

4x^2 + 25x - 21 = -5x^2 - 14x - 3

Move it all to one side =

4x^2 + 25x - 21 (+5x^2 + 14x + 3)

9x^2 + 39x - 18

I then try to factorise it...
9 x - 18 = -162... but I can't seem to factorise it, so that tells me I have gone wrong somewhere.

I know the answers are 1 and -1.

Can anyone give me a nudge in the right direction? thank you
This part is wrong.
4. (Original post by Tinkletea)
(x - 3)(1 - 5x)

x - 5x^2 - 3 - 15x ---> simplied too: -5x^2 - 14x - 3
Check this part.
5. (x - 3)(1 - 5x)
x - 5x^2 - 3 - 15x ---> simplied too: -5x^2 - 14x - 3
should be +15x

EDIT: triple-ninja'd? :/
6. (x - 3)(1 - 5x)
x x 1 = x
x x - 5x = -5x^2
-3 x 1 = -3
-3 x -5x = +15x

= -5x^2 + 16x - 3
Is that right, I forgot a negative x a negative is a positive oops

so
4x^2 + 25x - 21 (+5x^2 - 16x + 3)
9x^2 + 9x - 18

So 9 x -18 = -162
-9 x 18 = -162 (-9 + 18 = 9) Oh!

9x^2 - 9x + 18x - 18

9x(x - 1) +18(x - 1)

9x + 18 = 0 (-18 = 9x)
-18 / 9 = x = -2
x - 1 = 0 (+1 = x) = x = 1

Obviously, gone wrong again, since the answers are -1 and 1?
7. I've just solved it and your solutions are correct (sub them into the original equation and you'll see )
8. Subbing in x = -1 in the original equation yields me -7/6 = -2/3 which means it is not a solution. Subbing in both x=-2 and x=1 in the original equation makes the two sides equal to each other.
9. Not according to MyMaths

But ill take your word from it, I can relax now I have got over that one!

thanks all

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: April 11, 2013
Today on TSR

### Am I pregnant?

...or just paranoid?

### A robot wrote Harry Potter?

Discussions on TSR

• Latest
• ## See more of what you like on The Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

• Poll
Useful resources

### Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

### How to use LaTex

Writing equations the easy way

### Study habits of A* students

Top tips from students who have already aced their exams

## Groups associated with this forum:

View associated groups
Discussions on TSR

• Latest
• ## See more of what you like on The Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

• The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE

Reputation gems: You get these gems as you gain rep from other members for making good contributions and giving helpful advice.